Immediate effects of phototherapy on sleep in very preterm neonates: an observational study. (3rd May 2016) - Cremer, Martin; Jost, Kerstin; Gensmer, Anna; Pramana, Isabelle; Delgado‐Eckert, Edgar; Frey, Urs; Schulzke, Sven M.; Datta, Alexandre N.
Summary: Process C (internal clock) and Process S (sleep–wake homeostasis) are the basis of sleep–wake regulation. In the last trimester of pregnancy, foetal heart rate is synchronized with the maternal circadian rhythm. At birth, this interaction fails and an ultradian rhythm appears. Light exposure is a strong factor influencing the synchronization of sleep–wake processes. However, little is known about the effects of phototherapy on the sleep rhythm of premature babies. It was hypothesized that sleep in preterm infants would not differ during phototherapy, but that a maturation effect would be seen. Sleep states were studied in 38 infants born < 32 weeks gestational age and/or < 1 500 g birth weight. Videos of 3 h were taken over the first 5 days of life. Based on breathing and movement patterns, behavioural states were defined as: awake; active sleep; or quiet sleep. Videos with and without phototherapy were compared for amounts of quiet sleep and active states (awake + active sleep). No significant association between phototherapy and amount of quiet sleep was found ( P = 0.083). Analysis of videos in infants not under phototherapy revealed an increase in time spent awake with increasing gestational age. The current data suggest that the ultradian rhythm of preterm infants seems to be independent of phototherapy, supporting the notion that sleep rhythm in this population is mainly driven by their internal clock.